Solid electrolyte membrane and all-solid-state battery including the same

The use of a styrene-butadiene-styrene copolymer with 22 to 34% styrene content in solid electrolyte membranes addresses the limitations of conventional binders, enhancing ionic conductivity and flexibility, thus improving all-solid-state battery performance and energy density for diverse applications.

JP2025501606AActive Publication Date: 2025-01-22LG ENERGY SOLUTION LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024538210
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-16
Filing Date
2023-10-18
Publication Date
2025-01-22
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

Conventional lithium secondary batteries face limitations in energy density, safety, and flexibility due to the use of liquid electrolytes, while all-solid-state batteries suffer from lower energy density and potential short circuits with existing binder technologies, particularly with nitrile-butadiene rubber (NBR), hindering the development of flexible and high-energy density solid electrolyte membranes.

Method used

A solid electrolyte membrane for all-solid-state batteries is developed using a styrene-butadiene-styrene copolymer with a styrene content of 22 to 34% by weight, which enhances ionic conductivity and flexibility, allowing for the production of a free-standing film that can be easily integrated into all-solid-state batteries.

Benefits of technology

The proposed solid electrolyte membrane exhibits improved ionic conductivity and flexibility, enabling the production of all-solid-state batteries with enhanced energy density and reduced risk of short circuits, facilitating their application in various devices including electric vehicles and energy storage systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501606000001_ABST
    Figure 2025501606000001_ABST
Patent Text Reader

Abstract

The present invention relates to a solid electrolyte membrane for an all-solid-state battery, which comprises a binder containing 22 to 34% by weight of styrene relative to the total weight of a styrene-butadiene-styrene copolymer, and a solid electrolyte, and to an all-solid-state battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0153588 dated November 16, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a solid electrolyte membrane and an all-solid-state battery including the same. [Background technology]

[0003] A secondary battery is a device that converts external electrical energy into chemical energy, stores it, and produces electricity when needed. It is also called a rechargeable battery because it can be recharged multiple times. Commonly used secondary batteries include lead-acid batteries, nickel-cadmium batteries (NiCd), nickel-metal hydride batteries (NiMH), and lithium secondary batteries. Secondary batteries offer both economical and environmental advantages over disposable primary batteries.

[0004] Meanwhile, with the development of wireless communication technology, there is a demand for portable devices and automobile accessories to be lighter, thinner, and smaller, and the demand for secondary batteries to be used as energy sources for these devices is increasing. In particular, from the viewpoint of preventing environmental pollution, hybrid cars and electric cars have been put to practical use, and research has emerged on using secondary batteries in these next-generation automobile batteries to reduce manufacturing costs and weight and extend life. Among various secondary batteries, lithium secondary batteries, which are lightweight, have high energy density and operating potential, and have a long cycle life, have recently been in the spotlight.

[0005] In general, a lithium secondary battery is manufactured by mounting an electrode assembly including a negative electrode, a positive electrode, and a separator inside a cylindrical or rectangular metal can or a pouch-shaped case made of an aluminum laminate sheet, and injecting an electrolyte into the electrode assembly.

[0006] However, since lithium secondary batteries require a case with a certain space, such as a cylindrical, square, or pouch-shaped case, there are limitations on developing portable devices of various shapes. Therefore, a new type of lithium secondary battery that can be easily transformed is required. In particular, an electrolyte that is free from leakage and has excellent ionic conductivity is required as the electrolyte contained in the lithium secondary battery.

[0007] Conventionally, liquid electrolytes in which lithium salts are dissolved in non-aqueous organic solvents have been mainly used as electrolytes for lithium secondary batteries. However, such liquid electrolytes are likely to cause deterioration of electrode materials and volatilization of organic solvents, and may also cause combustion or explosion due to temperature rises in the surroundings and the battery itself, leading to the risk of leakage, making it difficult to realize various types of lithium secondary batteries with high safety.

[0008] On the other hand, all-solid-state batteries using solid electrolytes have the advantage that they do not use organic solvents and therefore allow the electrode assembly to be produced in a safe and simple manner.

[0009] However, all-solid-state batteries have limitations in that their actual energy density and output are not as good as those of conventional lithium secondary batteries that use liquid electrolytes. Because an electrolyte membrane containing a solid electrolyte is located between the positive and negative electrodes, all-solid-state batteries are larger in volume and heavier than conventional lithium secondary batteries, resulting in lower energy density per volume and energy density per weight. If the electrolyte membrane is made thinner to prevent this, a short circuit between the positive and negative electrodes may occur.

[0010] However, there are limitations with the current limited slurry solvent and binder technology. Conventionally, nitrile-butadiene rubber (NBR) has been mainly used as a binder for solid electrolyte membranes for all-solid-state batteries, but when manufacturing thin films, there are problems with moisture stability, mechanical properties, and manufacturing processability.

[0011] As described above, solid electrolyte membranes for all-solid-state batteries need to be manufactured as thin membranes in order to achieve high energy density and reduced resistance, and further need to satisfy the required properties in terms of bending properties, ionic conductivity, and the ability to be made large in area.

[0012] Therefore, there is a need to develop a solid electrolyte membrane for all-solid-state batteries that not only has excellent ionic conductivity but also has flexibility. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Korean Patent Publication No. 10-2021-0098246 Summary of the Invention [Problem to be solved by the invention]

[0014] Therefore, the present inventors have conducted extensive research to solve the above problems and have found that ionic conductivity and flexibility can be improved by adjusting the content of styrene in a styrene-butadiene-styrene copolymer as a binder, thereby completing the present invention.

[0015] Therefore, an object of the present invention is to provide a solid electrolyte membrane for an all-solid-state battery having excellent ionic conductivity and flexibility.

[0016] Another object of the present invention is to provide an all-solid-state battery including the solid electrolyte membrane. [Means for solving the problem]

[0017] In order to achieve the above objective, The present invention includes a solid electrolyte and a binder, the binder comprises a styrene-butadiene-styrene copolymer; The present invention provides a solid electrolyte membrane for an all-solid-state battery, wherein the styrene content is 22 to 34% by weight based on the total weight of the styrene-butadiene-styrene copolymer.

[0018] The present invention also provides an all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between them, wherein the solid electrolyte membrane is the solid electrolyte membrane of the present invention. Effect of the Invention

[0019] The solid electrolyte membrane for an all-solid-state battery of the present invention includes a styrene-butadiene-styrene copolymer as a binder, and the content of styrene in the copolymer can be adjusted to exhibit excellent effects in ion conductivity and flexibility. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic diagram of an all-solid-state battery including a solid electrolyte membrane for an all-solid-state battery of the present invention. [Diagram 2] 1 is a photograph of a solid electrolyte membrane for an all-solid-state battery according to the present invention. [Diagram 3] 1 is a graph showing the ion conductivity of the solid electrolyte membranes for all-solid-state batteries of Examples 1-2 and Comparative Examples 1-3. [Figure 4] 1 is a photograph showing the measurement of flexibility of the solid electrolyte membrane for an all-solid-state battery of Example 1. [Diagram 5] 1 is a photograph showing the measurement of flexibility of the solid electrolyte membrane for an all-solid-state battery of Example 2. [Figure 6] 1 is a photograph showing the measurement of flexibility of a solid electrolyte membrane for an all-solid-state battery of Comparative Example 1. [Figure 7] 1 is a photograph showing the measurement of flexibility of a solid electrolyte membrane for an all-solid-state battery of Comparative Example 2. [Figure 8] 13 is a photograph showing the measurement of flexibility of the solid electrolyte membrane for an all-solid-state battery of Comparative Example 3. [Figure 9] 1 is a graph showing the measurement of the charge / discharge capacity of the all-solid-state battery of Experimental Example 2. [Figure 10] 1 is a graph showing the results of measuring the life characteristics of the all-solid-state battery of Experimental Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will now be described in more detail.

[0022] Furthermore, the terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meaning, but should be interpreted in a meaning and concept that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best explain his / her invention.

[0023] The terms used in this specification are merely used to describe specific embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include" or "have" specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and should be understood not to preclude the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0024] Lithium secondary batteries have been used in small areas such as mobile phones and laptops, but recently their application is expanding to medium and large areas such as electric vehicles and energy storage devices. In this case, unlike small areas, not only is the operating environment harsher, but more batteries must be used, so it is necessary to ensure stability as well as excellent performance.

[0025] Most lithium secondary batteries currently on the market use a liquid electrolyte in which lithium salt is dissolved in an organic solvent. The organic solvent contained in the liquid electrolyte is highly volatile and flammable, posing a potential risk of fire or explosion, and the risk of leakage, resulting in a lack of long-term reliability.

[0026] Therefore, development of all-solid-state batteries, which replace the liquid electrolyte of lithium secondary batteries with a solid electrolyte, is underway. Because all-solid-state batteries do not contain volatile organic solvents, they are free of the risk of explosion or fire, and are attracting attention as batteries that are economical, highly productive, and capable of producing high-output batteries.

[0027] In order to realize high energy density of all-solid-state batteries, it is necessary to prepare a thin solid electrolyte membrane. The solid electrolyte membrane is prepared by coating a slurry containing a particulate solid electrolyte and a binder on a release film, drying the slurry, and removing the release film. The dispersibility of the solid electrolyte, the feasibility of preparing a solid electrolyte membrane, and even the charge / discharge characteristics of the all-solid-state battery may differ depending on the physical properties of the binder.

[0028] Therefore, the present invention aims to provide a solid electrolyte membrane for an all-solid-state battery that has excellent ion conductivity by minimizing the decrease in ion conductivity and has excellent flexibility so that the all-solid-state battery can be easily manufactured.

[0029] The present invention includes a solid electrolyte and a binder, the binder comprises a styrene-butadiene-styrene copolymer; The present invention relates to a solid electrolyte membrane for an all-solid-state battery, wherein the styrene content is 22 to 34% by weight based on the total weight of the styrene-butadiene-styrene copolymer.

[0030] The solid electrolyte may include at least one selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte, and may preferably include a sulfide-based solid electrolyte. The solid electrolyte may be in the form of particles.

[0031] The sulfide-based solid electrolyte contains sulfur (S) and has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and may include Li-PS-based glass or Li-PS-based glass ceramic.

[0032] Specifically, the sulfide-based solid electrolyte may include one or more selected from the group consisting of Li6PS5Cl, Li6PS5Br, Li6PS5I, Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2S5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, and Li2S-GeS2-ZnS, and may preferably include one or more selected from the group consisting of Li6PS5Cl, Li6PS5Br, and Li6PS5I. The Li6PS5Cl, Li6PS5Br and Li6PS5I may be argyrodite type solid electrolytes. The sulfide-based solid electrolyte may be doped with a trace element, for example, Li6PS5Cl may be further doped with bromine (Br).

[0033] The polymer solid electrolyte is a composite of lithium salt and polymer resin, i.e., a polymer electrolyte material formed by adding polymer resin to a solvated lithium salt. -7 S / cm or more, preferably about 1x10 -5 It can exhibit ionic conductivity of more than S / cm.

[0034] Non-limiting examples of the polymer resin include polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, alkylene oxide derivatives such as polyethylene oxide, phosphate ester polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociation groups, etc., and the polymer electrolyte may include at least one of them. In addition, the polymer electrolyte may include at least one of them, such as branched copolymers in which amorphous polymers such as PMMA, polycarbonate, polysiloxane (pdms) and / or phosphazene are copolymerized with a PEO (poly ethylene oxide) main chain using a comonomer, comb-like polymers, and crosslinked polymers, as polymer resins.

[0035] In the electrolyte of the present invention, the above-mentioned lithium salt is an ionizable lithium salt, and Li + X - The anion of such a lithium salt is not particularly limited, but may be represented by F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C- , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , (CF3CF2SO2)2N - etc.

[0036] The oxide-based solid electrolyte may contain oxygen (O) and have the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. For example, LLTO-based compounds, Li6La2CaTa2O 12 , Li6La2ANb2O 12 (A is Ca or Sr), Li2Nd3TeSbO 12 , LiBO 2.5 N 0.5 , Li9SiAlO8, LAGP compounds, LATP compounds, Li 1+x Ti 2-x Al x S y (PO4) 3-y (where 0≦x≦1, 0≦y≦1), LiAl x Zr 2-x (PO4)3 (where 0≦x≦1), LiTi x Zr 2-x (PO4)3 (where 0≦x≦1), may contain one or more compounds selected from LISICON-based compounds, LIPON-based compounds, Perovskite-based compounds, Nasicon-based compounds, and LLZO-based compounds.

[0037] The binder may include a styrene-butadiene-styrene (SBS) copolymer, and the styrene-butadiene-styrene copolymer may be represented by the following Chemical Formula 1:

[0038] [Chemical formula 1] [ka]

[0039] The l, m and n are the same or different and are integers of 100 or more.

[0040] The styrene-butadiene-styrene copolymer does not react with the solid electrolyte and effectively binds the particulate solid electrolyte, thereby improving the ionic conductivity of the solid electrolyte membrane for the all-solid-state battery.

[0041] The solid electrolyte membrane for the all-solid-state battery also serves as a separator and is interposed between the positive and negative electrodes during the manufacture of the all-solid-state battery, and must not crack. In addition, if the solid electrolyte membrane for the all-solid-state battery is hard and easily broken, a short circuit in the all-solid-state battery may easily occur, so the solid electrolyte membrane must have excellent flexibility.

[0042] The solid electrolyte membrane for all-solid-state batteries of the present invention contains 22 to 34% by weight of styrene relative to the total weight of the styrene-butadiene-styrene copolymer, and thus can provide a solid electrolyte membrane for all-solid-state batteries having excellent ion conductivity and flexibility. In addition, the excellent flexibility allows a continuous process during the production of an all-solid-state battery containing the same, and has excellent processability.

[0043] The upper limit of the styrene content may be 31.5 wt%, 32 wt%, 33 wt%, or 34 wt%. The lower limit of the styrene content may be 22 wt%, 23 wt%, or 23.5 wt%. The styrene content may be within a range determined by combining the upper and lower limits.

[0044] If the styrene content is less than 22 wt% based on the total weight of the styrene-butadiene-styrene copolymer, the content of styrene with a rigid structure is low, and although the flexibility of the solid electrolyte membrane for all-solid-state batteries can be ensured, there is a problem of low ion conductivity. Also, if the styrene content is more than 34 wt% based on the total weight of the styrene-butadiene-styrene copolymer, the conjugated structure of styrene can provide high ion conductivity, but the rigid structure of styrene means that flexibility cannot be ensured, and problems such as cracking occur.

[0045] Therefore, by containing 22 to 34% by weight of styrene with respect to the total weight of the copolymer, a solid electrolyte membrane for an all-solid-state battery having excellent ionic conductivity and flexibility can be provided.

[0046] In addition, the solid electrolyte may be included in an amount of 95 to 99.5 wt % and the binder may be included in an amount of 0.5 to 5 wt % based on the total weight of the solid electrolyte membrane for the all-solid-state battery. By including the solid electrolyte and the binder as described above, it is possible to prepare a solid electrolyte membrane for the all-solid-state battery that can be maintained in a film form while minimizing the content of the binder that acts as a resistance to ion conductivity.

[0047] The solid electrolyte membrane for an all-solid-state battery may be a free-standing (also called "self-supporting") film. The free-standing film means one that maintains its shape without the provision of a support. The free-standing film-like solid electrolyte membrane for an all-solid-state battery may be used in the manufacturing process of an all-solid-state battery without the requirement of any external support.

[0048] The solid electrolyte membrane for all-solid-state batteries may have a thickness of 30 to 200 μm, preferably 50 to 100 μm. By having the above thickness, the membrane can be applied to all-solid-state batteries, and can exhibit excellent effects in ion conductivity and flexibility.

[0049] The solid electrolyte membrane for an all-solid-state battery may have an ionic conductivity of 1.2 to 10 mS / cm, preferably 1.5 to 3 mS / cm.

[0050] The solid electrolyte membrane for the all-solid-state battery may be manufactured by mixing a solid electrolyte, a styrene-butadiene-styrene copolymer, and a solvent to prepare a slurry, applying the slurry to one side of a release film, drying the slurry, and then removing the release film. In this case, the solvent may be any solvent that does not react with the styrene-butadiene-styrene copolymer and the solid electrolyte without any particular limitation.

[0051] The present invention also relates to an all-solid-state battery including a positive electrode, a negative electrode, and a solid electrolyte membrane interposed therebetween, and the solid electrolyte membrane may be the solid electrolyte membrane of the present invention described above.

[0052] The all-solid-state battery is a lithium secondary battery, and is not limited to a positive electrode or a negative electrode, and may be a lithium-air battery, a lithium oxide battery, a lithium-sulfur battery, or a lithium metal battery.

[0053] The positive electrode may include a positive electrode current collector and a positive electrode active material coated on one or both sides of the positive electrode current collector.

[0054] The positive electrode current collector is for supporting the positive electrode active material, and is not particularly limited as long as it has excellent conductivity and is electrochemically stable in the voltage range of a lithium secondary battery. For example, the positive electrode current collector may be any one metal selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, their alloys, and combinations thereof, and the stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may preferably be an aluminum-cadmium alloy, or may be calcined carbon, a non-conductive polymer surface-treated with a conductive material, or a conductive polymer.

[0055] The positive electrode current collector may have fine projections and recesses on its surface to strengthen the bonding force with the negative electrode active material, and may be in various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.

[0056] The positive electrode active material may include a positive electrode active material, and optionally a conductive material and a binder.

[0057] The positive electrode active material may vary depending on the type of all-solid-state battery. For example, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-x O4 (0≦x≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by O2 (M=Co, Mn, Al, Cu, Fe, Mg, B or Ga; 0.01≦x≦0.3); chemical formula LiMn 2-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (M=Fe, Co, Ni, Cu, or Zn) or LiNi x Mn 2-x Lithium manganese oxide with spinel structure represented by O4; LiCoPO4; LiFePO4; Elemental sulfur (S8); Li2S n (n=1), organic sulfur compounds or carbon-sulfur polymers (C2S x ) n The present invention is not limited to these, but may include sulfur-based compounds such as: x=2.5 to 50, n=2).

[0058] The conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from a current collector to the positive electrode active material. Any conductive material that does not cause a chemical reaction in a lithium secondary battery and has porosity and conductivity may be used without limitation.

[0059] For example, the conductive material may be a carbon-based material having porosity, and examples of such carbon-based materials include carbon black, graphite, graphene, activated carbon, carbon fiber, etc., metallic fibers such as metal mesh, metallic powders such as copper, silver, nickel, aluminum, etc., and organic conductive materials such as polyphenylene derivatives. The conductive materials may be used alone or in combination.

[0060] Currently, commercially available conductive materials include acetylene black (Chevron Chemical Company and Gulf Oil Company products, etc.), Ketjen Black EC (Armak Company product), Vulcan XC-72 (Cabot Company product), and Super P (MMM Company product), etc. Examples include acetylene black, carbon black, and graphite.

[0061] The positive electrode may further include a binder. The binder enhances the binding strength between the components constituting the positive electrode and between the components and the current collector, and any binder known in the art may be used.

[0062] For example, the binder may be one or a mixture or copolymer of two or more selected from the group consisting of: fluororesin-based binders including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0063] The negative electrode may include a negative electrode current collector and a negative electrode active material located on the negative electrode current collector. Similarly to the positive electrode, the negative electrode may include a conductive material and a binder as necessary. In this case, the negative electrode current collector, the conductive material, and the binder are as described above.

[0064] The negative electrode active material is a lithium ion (Li + Any material capable of reversibly intercalating or deintercalating lithium ions, or capable of reversibly forming a lithium-containing compound by reacting with lithium ions, is usable.

[0065] For example, the negative electrode active material may be one or more carbon-based materials selected from the group consisting of crystalline artificial graphite, crystalline natural graphite, amorphous hard carbon, low crystalline soft carbon, carbon black, acetylene black, ketjen black, super P, graphene, and fibrous carbon, Si-based materials, Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me´y O z Examples of suitable materials include, but are not limited to, metal composite oxides such as (Me: Mn, Fe, Pb, Ge; Me´: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogens; 0≦x≦1; 1≦y≦3; 1≦z≦8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxide; and lithium titanium oxide.

[0066] The production method of the all-solid-state battery is not particularly limited in the present invention, and any known method may be used.

[0067] As an example, a solid electrolyte membrane is placed between a positive electrode and a negative electrode, and then the membrane is compression molded to assemble a cell. The assembled cell is placed in an exterior material and then sealed by heat compression or the like. As the exterior material, a laminate pack of aluminum, stainless steel, or the like, or a metallic container such as a cylindrical or rectangular container may be used.

[0068] For example, the positive and negative electrodes are manufactured through a slurry coating process in which a slurry composition containing the respective electrode active materials, a solvent, and a binder is prepared, coated, and then dried.

[0069] The electrode slurry may be coated on the current collector by distributing the electrode slurry on the current collector and then dispersing it uniformly using a doctor blade, die casting, comma coating, screen printing, etc. Alternatively, the electrode slurry may be molded on a separate substrate and then bonded to the current collector by pressing or lamination. In this case, the thickness of the final coating can be adjusted by adjusting the concentration of the slurry solution or the number of coatings.

[0070] The drying step is a step of removing the solvent and water in the slurry in order to dry the slurry coated on the metal current collector, and may vary depending on the solvent used. For example, it is performed in a vacuum oven at 50 to 200°C. Examples of drying methods include drying with warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams. The drying time is not particularly limited, but is usually performed within a range of 30 seconds to 24 hours.

[0071] After the drying process, a cooling process may be further included, and the cooling process may be slow cooling to room temperature so that the recrystallization structure of the binder is well formed.

[0072] If necessary, a rolling process may be performed after the drying process to compress the electrode to a desired thickness by passing it between two rolls heated to a high temperature in order to increase the capacity density of the electrode and the adhesion between the current collector and the active material. The rolling process is not particularly limited in the present invention, and any known pressing process may be used. For example, the rolling process is performed by passing the electrode between rotating rolls or using a flat plate press.

[0073] The shape of the all-solid-state battery is not particularly limited, and may be in various shapes such as a cylindrical shape, a laminated shape, or a coin shape.

[0074] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical spirit of the present invention. Naturally, these changes and modifications also fall within the scope of the appended claims.

[0075] <Production of solid electrolyte membranes for all-solid-state batteries> Example 1. A slurry was prepared by mixing argyrodite (Li6PS5Cl), a styrene-butadiene-styrene copolymer, and isobutyl isobutyrate as a solid electrolyte. The styrene-butadiene-styrene copolymer contained 23.5% by weight of styrene (molecular weight 50,000) based on the total weight of the styrene-butadiene-styrene copolymer.

[0076] Polyethylene terephthalate was used as a release film, and the slurry was coated on the release film, which was then dried at room temperature for 2 hours and then dried in a vacuum oven at 70°C for 5 hours. The release film was then removed to produce a free-standing solid electrolyte membrane for all-solid-state batteries.

[0077] The solid electrolyte membrane for the all-solid-state battery contained 99% by weight of argyrodite and 1% by weight of styrene-butadiene-styrene copolymer based on the total weight of the all-solid-state battery solid electrolyte membrane, and had a thickness of 100 μm.

[0078] Example 2. A solid electrolyte membrane for an all-solid-state battery was prepared in the same manner as in Example 1, except that a styrene-butadiene-styrene copolymer (molecular weight 50,000) containing 31.5% by weight of styrene based on the total weight of the styrene-butadiene-styrene copolymer was used. The thickness of the solid electrolyte membrane for an all-solid-state battery was 100 μm.

[0079] Comparative Example 1 A solid electrolyte membrane for an all-solid-state battery was prepared in the same manner as in Example 1, except that a styrene-butadiene-styrene copolymer (molecular weight 50,000) containing 21% by weight of styrene based on the total weight of the styrene-butadiene-styrene copolymer was used. The thickness of the solid electrolyte membrane for an all-solid-state battery was 100 μm.

[0080] Comparative Example 2 A solid electrolyte membrane for an all-solid-state battery was prepared in the same manner as in Example 1, except that a styrene-butadiene-styrene copolymer (molecular weight 50,000) containing 40.5 wt% of styrene based on the total weight of the styrene-butadiene-styrene copolymer was used. The thickness of the solid electrolyte membrane for an all-solid-state battery was 100 μm.

[0081] Comparative Example 3. A solid electrolyte membrane for an all-solid-state battery was prepared in the same manner as in Example 1, except that a styrene-butadiene-styrene copolymer (molecular weight 50,000) containing 35% by weight of styrene based on the total weight of the styrene-butadiene-styrene copolymer was used. The thickness of the solid electrolyte membrane for an all-solid-state battery was 100 μm.

[0082] Experimental Example 1. Measurement of ionic conductivity and flexibility of solid electrolyte membrane for all-solid-state batteries The ionic conductivity and flexibility of the solid electrolyte membranes for all-solid-state batteries prepared in Examples 1 and 2 and Comparative Examples 1 to 3 were measured.

[0083] The ionic conductivity was measured by assembling a jig cell by placing aluminum foil on the upper and lower surfaces of the solid electrolyte membrane for the all-solid-state battery, and then applying a pressure of 360 MPa.

[0084] Flexibility was evaluated by observing whether or not cracks occurred when the solid electrolyte membrane for all-solid-state batteries was wound around a mandrel with a diameter of 2 mm.

[0085] The results of the ionic conductivity and flexibility are shown in Table 1 below and in FIGS.

[0086] [Table 1]

[0087] From the results in Table 1, it can be seen that Examples 1 and 2, which contain 22 to 34% by weight of styrene relative to the total weight of the styrene-butadiene-styrene copolymer, exhibit excellent ion conductivity, are free from cracks, and exhibit excellent flexibility.

[0088] In Comparative Example 1, the content of styrene was less than 22% by weight relative to the total weight of the styrene-butadiene-styrene copolymer, so no cracks were generated and flexibility was ensured, but the ion conductivity was poor.

[0089] Comparative Examples 2 and 3 contained more than 34% by weight of styrene relative to the total weight of the styrene-butadiene-styrene copolymer, and therefore showed better ionic conductivity than the Examples. However, it was confirmed that cracks occurred and the samples lacked flexibility.

[0090] Therefore, it is found that a solid electrolyte membrane for an all-solid-state battery containing 22 to 34% by weight of styrene with respect to the total weight of the styrene-butadiene-styrene copolymer has excellent ion conductivity and flexibility.

[0091] Experimental example 2: Evaluation of charge / discharge characteristics of all-solid-state batteries A positive electrode active material (NCM 811), a conductive material (carbon fiber), a solid electrolyte (Li6PS5Cl) and a binder (polytetrafluoroethylene) were mixed in a weight ratio of 84:0.2:14.8:1, and the mixture was rolled to prepare a positive electrode.

[0092] A mixture of anode active material (carbon black) and binder (polyvinylidene fluoride) was applied to a thickness of 150 μm on a 10 μm thick SUS negative electrode current collector to manufacture the negative electrode.

[0093] The solid electrolyte membranes for all-solid-state batteries prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were interposed between the positive electrode and the negative electrode, respectively, and then pressurized to prepare mono-cell type all-solid-state batteries.

[0094] Each of the all-solid-state batteries was repeatedly charged and discharged at 3.0 to 4.25 V and 1 C, and the charge and discharge characteristics of the all-solid-state batteries of Examples 1 and 2 and Comparative Examples 1 and 2 were measured, and the results are shown in FIGS.

[0095] From the results in FIG. 9, the initial charge / discharge capacities of the all-solid-state batteries of Examples 1 and 2 and Comparative Examples 1 and 2 showed similar results.

[0096] From the results of FIG. 10, the higher the content of styrene relative to the total weight of the styrene-butadiene-styrene copolymer, the better the life characteristics. That is, Comparative Example 2, which has the highest content of styrene, showed the best life characteristics, and Comparative Example 1, which has the lowest content of styrene, showed the worst life characteristics. This result is expected because the higher the content of styrene, the higher the ionic conductivity. However, Comparative Example 2 contains more than 34 wt % of styrene relative to the total weight of the styrene-butadiene-styrene copolymer, and showed poor flexibility such as cracking in the results of Experimental Example 1. As a result, it is not easy to manufacture an all-solid-state battery using the solid electrolyte membrane for an all-solid-state battery of Comparative Example 2, and even after the manufacture of the all-solid-state battery, the solid electrolyte membrane cannot maintain its shape and cracks, resulting in a high initial failure rate such as a short circuit occurring during initial charging.

[0097] Therefore, it can be seen that when the styrene content is 22 to 34 wt % relative to the total weight of the styrene-butadiene-styrene copolymer, the solid electrolyte membrane for the all-solid-state battery can have excellent ion conductivity and flexibility, thereby improving the charge / discharge characteristics of the all-solid-state battery.

Claims

1. Contains a solid electrolyte and a binder. the binder comprises a styrene-butadiene-styrene copolymer; The solid electrolyte membrane for an all-solid-state battery contains 22 to 34% by weight of styrene relative to the total weight of the styrene-butadiene-styrene copolymer.

2. 2. The solid electrolyte membrane for an all-solid-state battery according to claim 1, wherein the solid electrolyte is contained in an amount of 95 to 99.5% by weight and the binder is contained in an amount of 0.5 to 5% by weight, based on the total weight of the solid electrolyte membrane for an all-solid-state battery.

3. 2. The solid electrolyte membrane for an all-solid-state battery according to claim 1, wherein the solid electrolyte comprises at least one selected from the group consisting of a sulfide-based solid electrolyte, a polymer-based solid electrolyte, and an oxide-based solid electrolyte.

4. 2. The solid electrolyte membrane for an all-solid-state battery according to claim 1, wherein the solid electrolyte membrane for an all-solid-state battery is a free-standing film.

5. The solid electrolyte membrane for an all-solid-state battery according to claim 1, wherein the thickness of the solid electrolyte membrane for an all-solid-state battery is 30 to 200 μm.

6. The solid electrolyte membrane for an all-solid-state battery according to claim 1, wherein the ion conductivity of the solid electrolyte membrane for an all-solid-state battery is 1.2 to 10 mS / cm.

7. An all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between the positive electrode and the negative electrode, The solid electrolyte membrane according to any one of claims 1 to 6, wherein the solid electrolyte membrane is an all-solid-state battery.

Citation Information

Patent Citations

  • Composite related to extrusion polyether and use of the composite for electrochemical generator

    JP1995161363A

  • All-solid secondary battery and method of preparing same

    US20210242490A1

  • Binder for all-solid-state batteries, binder composition for all-solid-state batteries and method for producing binder composition for all-solid-state batteries

    WO2018163776A1

  • All Solid secondary battery, and Method for preparing the same

    KR1020210098246A